Anatomical and Histological Features of the Tongue Wild Boar (Sus scrofa) from Timor Island - Harum, Aurelia Bebonita; Inggrid Trinidad Maha; Nitbani, Heny; Filphin Adolfin Amalo; Selan, Yulfia Nellymalik; Jacob, Jois Moriani (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
The tongue is a complementary organ owned by living things that easily moves and fills the oral cavity when the upper and lower jaw teeth meet. This study aims to determine the anatomical structure and histology of the tongue in wild boar (Sus scrofa) from the Island of Timor. Tongue organs were collected from three healthy wild boars. Animals were slaughtered and necropsied. Macroscopic observations were made; length, width, and thickness were measured, and the tongue tissue was cut into several parts, namely the apex lingua, corpus lingua, and radix lingua, to be fixed in 10% formalin. Furthermore, Hematoxylin-Eosin (HE) staining was performed. The results showed that the dorsal surface has four types of papillae, namely circumvallate papillae, conical papillae, foliate papillae, fungiform papillae, and filiform papillae. The tongue muscles of wild boar were found to be m. longitudinalis, m. transversus, and m. verticalis. Conical papillae are conical with a blunt tip. Foliate papillae are located on the lateral-radix of the tongue. Fungiform papillae have a dome-like oval shape. Filiform papillae have an elongated cylindrical shape with a blunt tip. The size of the filiform papillae at the corpus of the tongue is larger than at the apex of the tongue.